2021
DOI: 10.1007/s00401-021-02348-6
|View full text |Cite
|
Sign up to set email alerts
|

Seizure-mediated iron accumulation and dysregulated iron metabolism after status epilepticus and in temporal lobe epilepsy

Abstract: Neuronal dysfunction due to iron accumulation in conjunction with reactive oxygen species (ROS) could represent an important, yet underappreciated, component of the epileptogenic process. However, to date, alterations in iron metabolism in the epileptogenic brain have not been addressed in detail. Iron-related neuropathology and antioxidant metabolic processes were investigated in resected brain tissue from patients with temporal lobe epilepsy and hippocampal sclerosis (TLE-HS), post-mortem brain tissue from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 101 publications
1
30
0
Order By: Relevance
“…Recent research demonstrated that iron dyshomeostasis plays an important role in epilepsy and depression. [36,37] Generally, IRPs (IRP1 and IRP2) sense the iron concentration and increase intracellular active iron via upregulating TfR1, downregulating FTH1, and FPN1. However, an abnormal increase in IRPs can lead to intracellular iron accumulation, thereby promoting ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research demonstrated that iron dyshomeostasis plays an important role in epilepsy and depression. [36,37] Generally, IRPs (IRP1 and IRP2) sense the iron concentration and increase intracellular active iron via upregulating TfR1, downregulating FTH1, and FPN1. However, an abnormal increase in IRPs can lead to intracellular iron accumulation, thereby promoting ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Iron metabolism in the brain is closely related to brain development and function. Past studies have confirmed a close relationship between iron levels and epilepsy ( Cai and Yang, 2021 ; Zimmer et al, 2021 ). Intracortical injections of Fe 3+ can induce seizures ( Das et al, 2017 ).…”
Section: Discussionmentioning
confidence: 86%
“…It indicated that PDPLA/DFO alleviated iron overload during Wallerian Degeneration. The imbalance of iron homeostasis causes neuronal dysfunction, and iron accumulation causes a continuous pro-inflammatory environment [ 55 ]. According to morphological analysis, nerve respond differently to WD among groups.…”
Section: Resultsmentioning
confidence: 99%